Calculation of rigid-body conformational changes using restraint-driven Cartesian transformations. - Sompornpisut, P (2001)
We present an approach for calculating conformational changes in membrane proteins using limited distance information. The method, named restraint-driven Cartesian transformations, involves 1) the use of relative distance changes; 2) the systematic sampling of rigid body movements in Cartesian space; 3) a penalty evaluation; and 4) model refinement using energy minimization. As a test case, we have analyzed the structural basis of activation gating in the Streptomyces lividans potassium channel (KcsA). A total of 10 pairs of distance restraints derived from site-directed spin labeling and electron paramagnetic resonance (SDSL-EPR) spectra were used to calculate the open conformation of the second transmembrane domains of KcsA (TM2). The SDSL-EPR based structure reveals a gating mechanism consistent with a scissoring-type motion of the TM2 segments that includes a pivot point near middle of the helix. The present approach considerably reduces the amount of time and effort required to establish the overall nature of conformational changes in membrane proteins. It is expected that this approach can be implemented into restrained molecular dynamics protocol to calculate the structure and conformational changes in a variety of membrane protein systems.